Management of the dead and missing people in the Easter bombings in Colombo, Sri Lanka / Jayanie Weeratna and Ajith Tennakoon - Weeratna, Jayanie; Tennakoon, Ajith (Faculty of Medicine, 2021)
Identification of the victims is considered as one of the most important initial steps in the management of a mass disaster. Comparison of ante-mortem and post-mortem fingerprints (ridgeology), dental data and DNA profiles have been recognized as primary identification methods for Disaster Victim Identification (DVI). However, facial recognition and personal belongings are the widely used tools of identification in large disasters. A series of bombings hit Sri Lanka on the morning of 21 st of April 2019. In the city of Colombo around 131 people died. Most of the identifications were achieved through visual recognition, with a minor percentage by odontology, genetics and fingerprints. The procedure adopted in the response to the disaster is described in this paper highlighting the importance of advanced preparedness, inter-institutional cooperation, the empathetic approach in caring for the grieving families and the procedure to adopt in visual recognition in DVI.